PEMANFAATAN BUAH MENJADI MINUMAN SMOOTHIES KEKINIAN DALAM MEMENUHI KEBUTUHAN NUTRISI - Pahrul Pahrul; Mahmuddin Mahmuddin; Mitha Evalista; Herawan Hisanan; Irfan Yunus (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
The creative industry in Indonesia has grown rapidly in recent years, resulting in increasingly intense trade competition and various innovations in product marketing. This research focuses on the use of fruit into smoothies The condition of urban communities with very high mobility which often demands practicality is also the background for the formation of smoothies businesses where people can easily get healthy and refreshing drinks without the hassle of making them themselves and made more varied with additional toppings. The fruit smoothies business offers a great opportunity to meet the body's nutritional needs while also becoming a profitable business. Fruits that contain rich vitamins, fiber, and antioxidants are beneficial for health. Through smoothies, these nutrients can be served in a delicious and practical form.